2007
DOI: 10.1021/om7003749
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Theoretical−Experimental Study of the Inclusion of Niobocene Dichloride in Native and Permethylated β-Cyclodextrins

Abstract: Inclusion complexes comprising niobocene dichloride, Cp 2 NbCl 2 , and either native -cyclodextrin ( -CD) or permethylated -CD (TRIMEB) were prepared with a host:guest molar ratio of 1:1. The adducts were characterized in the solid state by powder X-ray diffraction (XRD), thermogravimetric analysis (TGA), 13 C{ 1 H} CP/MAS NMR, FTIR, and FT Raman spectroscopies. Ab initio calculations were performed in order to elucidate the possible inclusion geometries and calculate vibrational frequencies for Cp 2 NbCl 2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 83 publications
4
23
0
Order By: Relevance
“…Nevertheless, we found that it works particularly well for the methylated cyclodextrin, TRIMEB, due to its high solubility in these media. In fact, the same method has been previously successfully employed by some of us (Braga et al 2006a;Pereira et al 2007). The adduct b-CDÁ[Ru( [9]aneS 3 )phenCl]Cl (4) was prepared by co-dissolution in water/ethanol (50/50) followed by freeze-drying to obtain an orange microcrystalline solid.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, we found that it works particularly well for the methylated cyclodextrin, TRIMEB, due to its high solubility in these media. In fact, the same method has been previously successfully employed by some of us (Braga et al 2006a;Pereira et al 2007). The adduct b-CDÁ[Ru( [9]aneS 3 )phenCl]Cl (4) was prepared by co-dissolution in water/ethanol (50/50) followed by freeze-drying to obtain an orange microcrystalline solid.…”
Section: Resultsmentioning
confidence: 92%
“…Recent work on CD inclusion of the compounds Cp 2 MCl 2 (Cp = cyclopentadienyl, M = Nb, Mo) (Pereira et al 2007;Braga et al 2005Braga et al , 2001 showed an enhanced antitumoral action, in particular for TRIMEBÁCp 2 MoCl 2 (Braga et al 2005). b-CD was also shown to enhance the cytotoxic activity of trans Pt(dipyridine)Cl 2 by improvement of its aqueous solubility (Horvath et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On a recent study, Goncalves and co-workers found, using ab initio calculations, that geometries A and B as well as a third geometry where the chloride is inserted into the cavity with a shallow penetration of the Cp rings could exist at room temperature. [34] The most likely geometry of the CD-Cp 2 VCl 2 host-guest complex will be investigated by molecular mechanics calculation.…”
Section: Resultsmentioning
confidence: 99%
“…[46] Today, hundreds of computational calculations describe drug-CD complexes reports. Table 1 classifies a number of present research studies in this field: molecular docking, [47][48][49] MD, [50][51][52][53] quantitative structure-activity/ property relationships (QSARs/QSPRs), [54][55][56] quantum mechanics (QM), [57][58][59] Monte Carlo (MC) simulations, [60][61][62] and machine learning.…”
Section: In Silico Methods For Discovery Of Cyclodextrinsmentioning
confidence: 99%
“…β-CD and four derivatives of β-CD Luteolin [47] Molecular docking HP-β-CD and methylated β-CD Voriconazole [58] β-CD 4,4′-Dihydroxybiphenyl [59] β-CD 57 Guest molecules [50] Molecular dynamics (MD) β-and γ-CD Amphotericin B [51] α-, β-, and γ-CD Cumene hydroperoxide [52] α-and β-CD 1-Alkanols, substituted phenols, and substituted imidazoles [53] α-CD Benzene derivatives [54] Quantitative structure-activity/ property relationships (QSARs/QSPRs) β-CD Multiple compounds [55] β-CD 233 Molecules [56] β-CD Dopamine and epinephrine [57] Quantum mechanics (QM) α-CD Carboplatin, oxaliplatin, nedaplatin [58] β-CD Aflatoxin B1 [59] β-CD Praziquantel [60] Monte Carlo (MC) simulations β-CD and methylated β-CD Niobocene dichloride [61] α-CD Water [62] Sulfobutylether β-CD Diverse organic molecules [63] Machine learning…”
Section: Methodsmentioning
confidence: 99%